Operando sob a luz do decoro albertiano: do prépon à racionalidade conveniente em Loos - Eduardo Campos Lamassa (2017)
Classical antiquity gives us the essence of decorum familiar to us for centuries. Convenience is the basic principle of decorum. Decorum comes from the Greek prepon, which already refers to what is appropriate to men and to a situation. Alberti presents us his concept of decorum in De Re Aedificatoria, which is also the central theme in this dissertation. After finding the decorum in Plato, Aristotle, Cicero, and Vitruvius, Alberti gives us so clearly a structuring approach to this knowledge that leaves us no doubt about the actuality of this principle and what we can learn from it. The Alberti Treaty is decisive for the understanding of the architectural and urban production based on the humanistic foundations of the Italian Renaissance. However, the structure intended for this dissertation is to extract the Alberti decorum in order to solidify it as an operator for critical reflection on objects and subjects of architecture and urbanism in the past and present. The literary work of the Viennese architect Adolf Loos, because of its complexity and pionerism, was chosen to be analyzed under the light of Alberti decorum. We hope under this propositions to have proven the contemporaneity of this concept.